Examine the Incidence of Neonatal Sepsis also Analyze the Risk Factors and Mortality Associated with Neonatal Sepsis (Medical Forum Monthly, 2024)
Objective: To examine the prevalence of neonatal sepsis and also determine the risk factors and mortality associated with this malignant disorder.Study Design: Prospective/ObservationalPlace and Duration of Study: This study was conducted at the Neonatal intensive care unit Pediatric Medicine, Bolan Medical Complex Hospital Quetta from June 2018 to December 2018.Materials and Methods: A total of 320 patients of both genders who were admitted to NICU were included in this study. Patients and mothers demographic were recorded. Diagnosis of neonatal sepsis was done clinically. Prevalence of neonatal sepsis was recorded. Risk factors and mortality associated to neonatal sepsis were examined.Results: Out of 320 patients, 60 (18.75%) diagnosed to have neonatal sepsis. In which 31 (51.67%) neonates were males while 48.33% were females. Maternal risk factors such as maternal age, PROM, delivery mode, history of UTI and history of antenatal care were highly associated to neonatal sepsis p-value 0.001. Neonatal risk factors such as birth weight, gestational age, birth asphyxia and resuscitation at birth were significantly associated to neonatal sepsis. 18 (30%) neonates died due to sepsis.Conclusion: The prevalence of neonatal sepsis and mortality associated to this malignant disorder in our setup was high and the most prevalent risk factors were birth weight, gestational age, birth asphyxia significantly associated to neonatal sepsis.